(untitled) (Al-Aasar, 2024)
The settlement of civil matters has always been by way of litigation—a legal proceeding within a system of law with its own rigid rules of procedure, opposing sides. It is likely very costly and emotionally demanding. Mediation, however, has come a long way and has become a very flexible, collaborative, cost-effective process that focuses on understanding and negotiating. This abstract will compare and contrast litigation and mediation, their weaknesses and strengths, and their application to various civil litigation. The emphasis of mediation is on confidentiality, party independence, and relationship rescue, and offers quicker solutions and reduced court system liability. Litigation is more time-consuming, more costly, and has binding decisions. Remedies are Useful when facts are complicated, and when legal rights are being infringed upon; they are enforceable, and procedural protections are useful. The comparative analysis indicates that in the vast majority of circumstances, mediation is the preferred mode of initiating civil litigation; however, in cases involving a power imbalance, public interest, and where precedent is a concern, litigation is necessary. The result of the research is that an inclusive dispute resolution mechanism, based on mediation, rather than litigation, could result in increased access to justice and in more efficient civil justice systems.